Peran Teknologi Informasi dalam Optimalisasi Manajemen Pelayanan Sosial: Pendekatan Studi Pustaka - Fadila Rahma Batubara; alya shalsabila lubis; Nazla zahara; Muthia El istiqomah siregar; Nelly Nadezda Berzanti Novna; Hairani Siregar (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Social services are an important element in realizing community welfare, especially for vulnerable groups. However, bureaucratic challenges, limited data, and inequality in access to services are still major obstacles in social service management. This study aims to explore the role of information technology (IT) in optimizing social service management through a literature study approach. The results of the literature review show that IT integration can improve accessibility, administrative efficiency, data accuracy, and transparency of social services. The implementation of systems such as Integrated Social Welfare Data (DTKS) and SIKS-NG shows a real contribution in accelerating real-time data collection and processing. In addition, the use of online applications and digital media expands the reach of services to remote areas and increases community participation. However, challenges such as limited infrastructure, human resources, and organizational culture are still obstacles. Therefore, adaptive policy support, human resource training, and equal distribution of digital infrastructure are needed to ensure the sustainability of digital transformation in social services. This study concludes that information technology is a strategic solution in building an inclusive, responsive, and quality social service system in the digital era.